CORROSION OF METALS AND METHODS OF PRESERVATION - U. A. Nurmamatov; A. D. Abdumoʻminov; R. M. Ashurov; A. Q. Togʻayev; D. S. Kurbanova (Web of Journals Publishing, 2024)
Corrosion is a natural process that transforms a refined metal into a chemically stable oxide. This is the gradual deterioration of materials (usually metal) as a result of a chemical or electrochemical reaction with the environment. Corrosion engineering is a field devoted to corrosion control and prevention.
Keywords: Alloying, painting, anti-corrosion, Corrosion of metal parts.